The Mediation Influence Of Value Relevance Of Accounting Information, Investment Decision And Dividend Policy On The Relationship Between Profitability And The Company’s Value - Harnovinsah Harnovinsah; Sustari Alamsyah (Jurnal Akuntansi, 2017)
This study aimed to analyze the influence of profitabilityon the company'svalue, and determine whether this influence intervenes the value relevance of accountinginformation, investment opportunities and dividend policy, assuming that investors actrationally so that the fundamental aspects of the financial statements become major factorin the shares investment decision. The contribution of this research is to provide input tothe management about the importance of maintaining and improving performance in orderto give satisfaction to investors and provide expectations for the return on investmentwhich can ultimately increase the company’s value. This study design is causality with theunit of analysis is the samples taken by purposive sampling technique on a population oflisted companies on the IDX Kompas 100index from 2011-2014. The analysis techniqueused is Path Analysis. The results from this study are: 1. Profitability has significant andpositive influence on the company’s value; 2. Profitability has no significant and positiveinfluence on the valuerelevance of accounting information; 3. Profitability has negativeand significant influence on investment opportunities; 4. Profitability has significant andpositive influence on the dividend policy; 5. The value relevance of accountinginformation has significant and negative influence on the company’s value; 6. Theinvestment opportunities have no significant and positive influence on company’s value;7. Dividend policy has no significant and positive influence on company’s value; 8. Thevalue relevanceof accounting information, investment opportunities and dividend policyhave not been able to mediate the influence of profitability on company’s value